Penyusunan Buku Pedoman Pengelolaan Arsip di Unit Kearsipan PT Semen Padang - Saputra, Rozy; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2020)
Abstract This paper is discusses the handbook of archive management at PT Semen Padang Achieves Unit. The method used in the handbook of archive management at PT Semen Padang Achieves is use descriptive method. The data collection is done by observation and interview.Based on the discussion above, it can be conclude that the steps in the handbook of archive management at PT Semen Padang Achieves Unit are as follows; (1) needs analysis, the author conducted interviews directly with employees at PT Semen Padang Achieves Unit regarding the use and obstacle encountered in using the archive classification code and design wished by the employees in the handbook; (2) product design, the author in advance makes the form of a chart; (3) product compilation; in this section the author do product compilation starting from collecting data information and composing a writing framework such as making book covers, preface, table of contents, main contents of the book, and cover.Keywords: preparation, archive, guide book.